2018
DOI: 10.4103/meajo.meajo_202_16
|View full text |Cite
|
Sign up to set email alerts
|

Causes of permanent severe visual impairment and blindness among Jordanian population

Abstract: PURPOSE:To report the causes of permanent severe visual impairment and blindness among Jordanian blind people.MATERIALS AND METHODS:This study was conducted on 1422 legally blind or worse vision people of all ages who attended the ophthalmic division of a medical committee for evaluation of disabled persons from July 2013 through November 2014. They were divided into two age groups: adult group (998 cases) and childhood group (<16 years, 424 cases). Patients presented reports from their ophthalmologists detail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Retinitis pigmentosa was the most common issue within retinal diseases, affecting 24.5% of patients. This is compatible with a Jordanian study that discussed the causes of severe visual impairment and blindness and found that retinitis pigmentosa was the most common cause of severe visual impairment among adults (29.7%), followed by diabetic retinopathy (19.9%) and glaucoma (15.8%) [50]. A study done by Mohidin and Yusof found that retinitis pigmentosa caused the highest percentage of the ocular pathologies for patients aged between 30-59 years old, followed by macular dystrophy and diabetic retinopathy [26].…”
Section: Discussionsupporting
confidence: 90%
“…Retinitis pigmentosa was the most common issue within retinal diseases, affecting 24.5% of patients. This is compatible with a Jordanian study that discussed the causes of severe visual impairment and blindness and found that retinitis pigmentosa was the most common cause of severe visual impairment among adults (29.7%), followed by diabetic retinopathy (19.9%) and glaucoma (15.8%) [50]. A study done by Mohidin and Yusof found that retinitis pigmentosa caused the highest percentage of the ocular pathologies for patients aged between 30-59 years old, followed by macular dystrophy and diabetic retinopathy [26].…”
Section: Discussionsupporting
confidence: 90%
“…Our findings rhyme with previous reports of causes of severe visual impairment and blindness in the country, again genetic diseases like retinitis pigmentosa being front and centre, followed by diabetic retinopathy and glaucoma. 31 Glatz et al published an excellent report about blindness and visual impairment in central Europe. Their findings showed that among the working-age adults and children in Austria, inherited retinal and choroidal diseases were the leading causes of visual impairment and blindness, drawing attention to further research in emerging treatments for those diseases.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Later studies from Kuwait, Lebanon, and Jordan support the same fact. 3,10,11 This might be explained the effort made by the government to treat infectious and other treatable eye diseases while consanguinity is still prevalent in the Saudi culture.…”
Section: Discussionmentioning
confidence: 99%